2016
DOI: 10.1007/112_2016_3
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin as a MicroRNA Regulator in Cancer: A Review

Abstract: Curcumin is a natural dietary polyphenol for which anti-tumor effects have been documented. Anti-inflammatory and antioxidant properties of curcumin, along with its immunomodulatory, proapoptotic, and antiangiogenic properties, are often referred to as the main mechanisms underlying the anti-tumor effects. At the molecular level, inhibition of NF-kB, Akt/PI3K, and MAPK pathways and enhancement of p53 are among the most important anticancer alterations induced by curcumin. Recent evidence has suggested that epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
130
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 200 publications
(130 citation statements)
references
References 111 publications
0
130
0
Order By: Relevance
“…MiRNAs employed several cellular and molecular targets such as PTEN, p53, Bcl‐2, MAPK, and Akt for exerting their effects (Keshavarzi, Darijani, et al, ; Keshavarzi, Sorayayi, et al, ; Mohammadi, Goodarzi, Jaafari, Mirzaei, & Mirzaei, ; Reza Mirzaei et al, ). Several studies indicated that curcumin could exert anti‐cancer properties via targeting miRNAs (Momtazi et al, ; Zhou et al, ). These studies revealed that curcumin could affect various miRNAs such as miR34a, miR‐21, miR‐181, miR‐7, and miR‐9 and miR‐200c (Momtazi et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs employed several cellular and molecular targets such as PTEN, p53, Bcl‐2, MAPK, and Akt for exerting their effects (Keshavarzi, Darijani, et al, ; Keshavarzi, Sorayayi, et al, ; Mohammadi, Goodarzi, Jaafari, Mirzaei, & Mirzaei, ; Reza Mirzaei et al, ). Several studies indicated that curcumin could exert anti‐cancer properties via targeting miRNAs (Momtazi et al, ; Zhou et al, ). These studies revealed that curcumin could affect various miRNAs such as miR34a, miR‐21, miR‐181, miR‐7, and miR‐9 and miR‐200c (Momtazi et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that curcumin could exert anti‐cancer properties via targeting miRNAs (Momtazi et al, ; Zhou et al, ). These studies revealed that curcumin could affect various miRNAs such as miR34a, miR‐21, miR‐181, miR‐7, and miR‐9 and miR‐200c (Momtazi et al, ; Zhou et al, ). Moreover, it has been shown that curcumin could affect the sensitivity to chemotherapy via targeting a variety of miRNAs such as miR‐186, miR‐21, and miR‐27a.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, curcumin has been shown to regulate multiple targets including NF-κB, Akt, Notch, mTOR, and Hh 2325. Recently, a growing body of evidence has implicated curcumin in regulating the expression of multiple miRNAs 26. Curcumin regulated miR-138 expression, leading to inhibition of cell proliferation and invasion in human osteosarcoma cells 27.…”
Section: Introductionmentioning
confidence: 99%
“…67 The ALDH1 expression is found to be increased in CSCs in inflammatory breast cancer. 66,76 CDF was reported to inhibit EZH2, Notch-1, CD44, EpCAM, and Nanog expression of CSCs in pancreatic cancer cells such as AsPC-1 and MiaPaCa-2 cells. Overexpression of CD133 has been frequently revealed in CSCs.…”
Section: On Csc Markersmentioning
confidence: 99%
“…103 In contrast, Subramaniam et al, 104 Zhou et al, 105 and Abdel Aziz et al 106 109,110 By affecting signaling pathways and CSC signature genes, miRNAs are also able to regulate CSC characteristics. 76,77,104,112,113 It has reported that miRNAs play pivotal roles in mediating inhibitory effects of curcumin on CSCs selfrenewal capacity, tumorigenic ability, and sphere formation. 76,77,104,112,113 It has reported that miRNAs play pivotal roles in mediating inhibitory effects of curcumin on CSCs selfrenewal capacity, tumorigenic ability, and sphere formation.…”
Section: The Effects Of Curcumin On Cscs Mediated By Modulation Of mentioning
confidence: 99%